Thermal Conductivity of Compacted GO-GMZ Bentonite Used as Buffer Material for a High-Level Radioactive Waste Repository. (4th September 2018) - Chen, Yong-Gui; Liu, Xue-Min; Mu, Xiang; Ye, Wei-Min; Cui, Yu-Jun; Chen, Bao; Wu, Dong-Bei
Abstract : In China, Gaomiaozi (GMZ) bentonite serves as a feasible buffer material in the high-level radioactive waste (HLW) repository, while its thermal conductivity is seen as a crucial parameter for the safety running of the HLW disposal. Due to the tremendous amount of heat released by such waste, the thermal conductivity of the buffer material is a crucial parameter for the safety running of the high-level radioactive waste disposal. For the purpose of improving its thermal conductivity, this research used the graphene oxide (GO) to modify the pure bentonite and then the nanocarbon-based bentonite (GO-GMZ) was obtained chemically. The thermal conductivity of this modified soil has been measured and investigated under various conditions in this study: the GO content, dry density, and water content. Researches confirm that the thermal conductivity of the modified bentonite is codetermined by the three conditions mentioned above, namely, the value of GO content, dry density, and water content. Besides, the study proposes an improved geometric mean model based on the special condition to predict the thermal conductivity of the compacted specimen; moreover, the calculated values are also compared with the experimental data.